Design of a Circular Patch Antenna with Parasitic Elements for 5G Applications - S. Lamultree; M. Phalla; P. Kunkritthanachai; C. Phongcharoenpanich (My University, 2023)
A design of a wideband bidirectional pattern antenna, accomplished by the integration of a circular patch, crescents as parasitic elements, encompassed by a circular ring adjoining the ground plane, to operate over the mid-band 5G sub-6 GHz applications is reported. It is come up with a copper grazed on FR4 substrate with relative permittivity of 4.3 and height of 1.6 mm. The proposed antenna is fed by a 50-ohm coplanar waveguide, which is printed on the same side of the radiating circular patch. A concise antenna model with dimensions of 45 × 45 × 0.6 mm3 was made up and investigated to affirm the simulation outcomes. Good consistency was confirmed between experimental and simulation results. The proposed antenna has the benefit of bidirectional pattern with a good gain of 5.24 dBi and wide bandwidth covering of 111.4% (1.81-6.36 GHz) — it is one of good postulants for 5G new radiation application especially for indoor environment, narrow, and long path services area like corridor, tunnel, and train station, etc.
Keywords: Ground plane; Patch antenna; Wideband; Antenna Design and Analysis